The brachiopod assemblage from the Maastrichtian white chalk at Chełm, eastern Poland: stratigraphical and palaeoecological implications - Marcin Machalski; Maria Aleksandra Bitner (Netherlands Journal of Geosciences, 2024)
Brachiopods from the lower upper Maastrichtian (Upper Cretaceous) white chalk succession exposed at Chełm (eastern Poland) comprise Lingula cretacea, Isocrania costata, Cryptoporella antiqua, Cretirhynchia sp., Neoliothyrina sp., Carneithyris sp., Terebratulina chrysalis, T. faujasi, T. longicollis, Terebratulina spp., Gisilina sp., Bronnothyris bronni, Magas chitoniformis, Leptothyrellopsis polonicus and ?Aemula sp. This assemblage is relatively poor in terms of taxonomic diversity and specimen abundance and is dominated by stratigraphically long-ranging species. It is best comparable to that from the micromorphic brachiopod Rugia tenuicostata–Meonia semiglobularis Zone as distinguished in the white chalk successions of Denmark and northern Germany, although this zone is usually placed in the upper lower Maastrichtian. The Chełm succession represents a relatively deep-water and ‘benthos-poor’ variety of white chalk deposited in the Boreal Chalk Sea of Europe. The brachiopod assemblage studied is typical of such a habitat, having been controlled largely by the low availability of minute skeletal substrates suitable for brachiopod settlement.